Electron microscopic studies of porcine sperm: changes during freezing and post-thawing - KHAN, M H; NATH, K C; NASKAR, S; DEKA, B C; KUMAR, SURESH (The Indian Journal of Animal Sciences, 2015)
The aim of the present study was to characterize the ultrastructural changes in boar spermatozoa at different stages during freezing (fresh undiluted semen, after holding at 24oC, after cooling to 5oC and after equilibration at 5oC) and after thawing using transmission electon microscopy (TEM). The study was also aimed to compare the sperm characteristics observed through conventional staining procedure with that of electron microscopy. A total of 72 ejaculates were collected from 6 Hampshire boars. Pooled semen was extended in BTSLEYG (Beltsvelli thawing solution lactose egg yok glycerol) extender and frozen in 0.5 ml French straws with conventional vapor freezing technique. Results of routine semen evaluation using conventional staining procedures seemed to be excellent. Microscopically assessed post-thaw percentage of progressively motile spermatozoa, live sperm count, spermatozoa with intact acrosome and hypo-osmotic reacted spermatozoa after thawing were 51.38±0.87, 56.83±0.74, 56.83±0.74 and 43.79±0.83, respectively. TEM examination of frozen–thawed semen revealed major changes in the morphology of spermatozoa localized predominantly within the acrosome and post acrosomal region of a head. Acrosomal and membrane integrity as observed through conventional statining and TEM was found to be 59.83±0.74 vs 37.88±8.85 and 43.79±0.83 vs 31.42±6.58%, respectively. It may be concluded that freezing and thawing of boar semen resulted into maximum sperm damage and electron microscopy revealed major changes in acrosome and plasma membrane which could not be seen with conventional staining procedure.